Lepton flavor violation with tau leptons - Heeck, Julian (SciPost physics proceedings, 2025)
We review the status and importance of lepton flavor violation with tauons, focusing on overlooked flavor-breaking patterns as well as tau-flavor violation in nucleon decays.